2009
DOI: 10.1016/j.brainres.2008.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Taste, olfactory and trigeminal neophobia in rats with forebrain lesions

Abstract: The present study was designed to examine whether lesions of the insular cortex (IC; Experiment 1), the basolateral amygdala (BLA) or medial amygdala (MeA; Experiment 2) influence the neophobic reactions to orally consumed liquid stimuli. Three different types of stimuli were used: taste (0.5% saccharin), olfactory (0.1% amyl acetate), and trigeminal (0.01 mM capsaicin). Rats with IC, BLA and MeA lesions showed normal responses to the olfactory and trigeminal stimuli. Each type of lesion, however, disrupted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 40 publications
13
58
0
Order By: Relevance
“…These structures also appear to be involved in the neophobic response itself. However, a deficit in the expression of the gustatory neophobic reaction was obtained only following permanent/neurotoxic lesions to the insular cortex, basolateral amygdala [13] and Prh (present results). In these three cases, permanent lesions produce elevated intake of the novel taste on initial encounter with no influence on the level of intake at asymptote.…”
Section: Discussionsupporting
confidence: 36%
See 1 more Smart Citation
“…These structures also appear to be involved in the neophobic response itself. However, a deficit in the expression of the gustatory neophobic reaction was obtained only following permanent/neurotoxic lesions to the insular cortex, basolateral amygdala [13] and Prh (present results). In these three cases, permanent lesions produce elevated intake of the novel taste on initial encounter with no influence on the level of intake at asymptote.…”
Section: Discussionsupporting
confidence: 36%
“…Using a variety of methods, including mostly c-fos expression and permanent or temporary lesions, it has been proposed that the basolateral amygdala and the insular cortex are the central components of this circuit, although the gustatory thalamus and the medial amygdala might also play a certain role [12][13][14][15]. Supporting the essential involvement of the basolateral amygdala and insular cortex, permanent lesions to this region http cause an elevated intake of the novel taste at the initial encounter and an intake comparable to that of controls at asymptote after presentation of the taste over several successive days [13,14,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Using our standard procedure (e.g., Lin, Roman, Arthurs & Reilly, 2012; Lin, Roman, St. Andre & Reilly, 2009), Lin, Amodeo, Arthurs and Reilly (2012) examined the neophobic reactions of separate groups of water-deprived rats to three tastants: saccharin, quinine and Polycose. Saccharin and quinine were chosen because they each show a pronounced neophobic reaction in terms of volume consumed; Polycose was included to extend the generality of the work of Barot and Bernstein (2005) that this tastant does not support a neophobic response.…”
Section: Lick Pattern Analysis and Palatabilitymentioning
confidence: 99%
“…IC lesions induce a consistent decrease in taste neophobia when the novel taste is presented in a familiar environment [146,[148][149][150][151][152]. As most studies so far have focused on taste memory, pharmacological interventions into the IC are performed only after taste presentation and very few -if any -pharmacological studies have investigated the neurotransmitters involved in taste neophobia per se.…”
Section: Role Of the Ic In Taste Functionmentioning
confidence: 99%
“…Dunn and Everitt (1988) [149] reported that BLA -but not CeA -lesions impair CTA. Furthermore, BLA lesions may impair taste neophobia [150] and arousal-induced taste neophobia, as well as passive avoidance [149]. Pharmacological BLA manipulations suggest a modulatory role in CTA after novel taste presentation, during visceral malaise and its association with the taste [193][194][195][196][197].…”
Section: The Role Of the Amygdala In Taste Functionmentioning
confidence: 99%